Modeling of non-stationary fluid inflow to a multisectional horizontal well - Morozov Petr E. (Общество с ограниченной ответственностью «Георесурсы», 2018)
For a more uniform production of oil reserves, horizontal wells are equipped with intelligent completion systems with remotely controlled multisection inflow control equipment and sensors to monitor pressure and temperature. A new semi-analytical solution of the problem of non-stationary fluid inflow to a multisectional horizontal well in an anisotropic reservoir is obtained. Typical curves of the pressure and pressure derivative in the isolated sections of the horizontal wellbore are built, taking into account the skin factor and the effect of the wellbore volume. It is shown that, for isolated sections of the horizontal wellbore with the help of profile reservoir separators and packers, the pressure response in inactive sections occurs with a delay. At the same time, inactive sections have little effect on the pressure change in the active section. With the decrease in the length of the reservoir uncouplers, the mutual influence of the active and inactive sections is strengthened. The effect of the fluid “crossflow” through the inactive sections of the horizontal wellbore has been revealed. A similar effect of fluid “crossflow” is observed in the trunk of a horizontal well after its stopping, as well as in the intervals of penetration by the stopped imperfect vertical well.
Keywords: multisectional horizontal well; intelligent well; semi-analytical solution; non-stationary inflow; pressure curve; skin factor; fluid “crossflow” effect